Verification of the effectiveness of the Integrated Product Development paradigm for the development of sports equipment -- A case study - Krüger, A.; Witte, K.; von Specht, E.; Vajna, S.; Edelmann-Nusser, J. (Procedia Engineering, 2010)
The sporting goods companies face significant challenges. To be successful on the market it is essential to follow a structured systematic product development process. A potential approach is the Integrated Product Development (IPD) paradigm. In this paper Insider Action Research (IAR) is used to verify the effectiveness of the IPD in a case study. It is shown that IPD is a potential development paradigm for the sporting goods industry to support a systematic development process for a successful product development in sports.